Relationship between sources of job stress, personality traits and job stress : the moderating role of coping strategies - Kumaresan V. Sathasivam (2016)
Job stress is ubiquitous in today's organizations, and the costs of these phenomena cut across all levels of society. In recent years, researchers considering job stress in the workplace have made great strides in understanding several aspects of the stress phenomenon in the field of organizational behavior. Thus, it becomes more important that the coping strategies of these job stresses are well explored and directly linked to individuals experiencing this situation, in order to ensure the right methods can be used for the best benefits in coping with work place stresses. This research presents an integration of past research and theory that models the relationship of antecedents of job stress and coping strategies among managers in electronics firms in Malaysia. A total of 400 electronic company managers participated in this study. This study is a survey using multiple questionnaires, namely, 'Job Stress' to measure the levels of job stress , 'Organizational Sources of Job Stress', to measure the sources of job stress , while 'NEO Five Factor Inventory' to gauge the personality of the manager and 'Coping Resources Inventory' to measure coping strategies. A set of demographic factors like gender, marital status and educational status, are also studied as influencing factors to job stress. Coping strategies in this study is positioned as a moderating variable. The implication of the study would be extremely beneficial for electronics organizations in not only identifying the organizational sources of job stress, but also to understand the personality behaviors of their management staffs. More importantly, this study recommends the best coping strategies for managers that would enable the leadership team in the electronics organizations to be able to handle job stress more efficiently. In the years to come, acknowledging the presence of job stress in major industries such as electronics industry in Malaysia, would become critical and the study would be able to help identify coping strategies that organizations can use to enable the best productivity from their management team. Contributions in of this study would prove essential to electronics firms in terms of managing their leadership workforce in terms of their stress management, productivity and wellbeing of the individuals. This will also allow companies to develop avenues to suit the rightful facilities and forums to address job stress for their employees that would result in work life effectiveness, which will result in highly motivated managers, highly productive organizations and a huge economy boost for the nation.